Reemergence of Human Monkeypox and Declining Population Immunity in the Context of Urbanization, Nigeria, 2017–2020 - Phi-Yen Nguyen; Whenayon Simeon Ajisegiri; Valentina Costantino; Abrar A. Chughtai; C. Raina MacIntyre (Emerging Infectious Diseases, 2021)
A monkeypox outbreak in Nigeria during 2017–2020 provides an illustrative case study for emerging zoonoses. We built a statistical model to simulate declining immunity from monkeypox at 2 levels: At the individual level, we used a constant rate of decline in immunity of 1.29% per year as smallpox vaccination rates fell. At the population level, the cohort of vaccinated residents decreased over time because of deaths and births. By 2016, only 10.1% of the total population in Nigeria was vaccinated against smallpox; the serologic immunity level was 25.7% among vaccinated persons and 2.6% in the overall population. The substantial resurgence of monkeypox in Nigeria in 2017 appears to have been driven by a combination of population growth, accumulation of unvaccinated cohorts, and decline in smallpox vaccine immunity. The expanding unvaccinated population means that entire households, not just children, are now more susceptible to monkeypox, increasing risk of human-to-human transmission.